2022
DOI: 10.1038/s41467-022-33899-1
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating cross-reactivity in polyclonal IgG1 responses against SARS-CoV-2 variants of concern

Abstract: Existing assays to measure antibody cross-reactivity against different SARS-CoV-2 spike (S) protein variants lack the discriminatory power to provide insights at the level of individual clones. Using a mass spectrometry-based approach we are able to monitor individual donors’ IgG1 clonal responses following a SARS-CoV-2 infection. We monitor the plasma clonal IgG1 profiles of 8 donors who had experienced an infection by either the wild type Wuhan Hu-1 virus or one of 3 VOCs (Alpha, Beta and Gamma). In these do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Spiked monoclonal antibodies of known concentration moreover enabled quantifying individual Fab molecules. Although differing variable domains may lead to Fab fragments with an identical mass and retention time and hence appear as the same Fab molecule, we expect such cases to be limited, given the low overlap between repertoires of different individuals observed in the current and previous studies 13 , 14 . Our validation of the approach further confirmed its specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Spiked monoclonal antibodies of known concentration moreover enabled quantifying individual Fab molecules. Although differing variable domains may lead to Fab fragments with an identical mass and retention time and hence appear as the same Fab molecule, we expect such cases to be limited, given the low overlap between repertoires of different individuals observed in the current and previous studies 13 , 14 . Our validation of the approach further confirmed its specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 73%
“…This liquid chromatography-mass spectrometry (LC-MS)-based Fab profiling approach selectively generates IgG1 Fab fragments from affinity enriched plasma IgG and analyzes these Fab molecules by LC-MS, thereby resolving the diversity of polyclonal antibody mixtures and repertoires based on the unique mass and retention time of each Fab molecule. The application of this approach revealed that plasma as well as virus-specific IgG1 repertoires are unique and polyclonal, with a few clones showing particularly high abundances 13 , 14 . This diversity of repertoires against infectious agents may, however, differ from that of autoreactive antibody repertoires as a result of the exclusion of autoreactive antibody clones by tolerance mechanisms as well as the different nature of and context in which autoantigens may be recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The IgdE treated samples were incubated on a thermal shaker at 37 °C for 16 h, and the BdpK-treated samples were incubated at 37 °C for 2 h. After incubation with either IgdE or BdpK, the flowthrough containing the Fab fragments generated from the bound IgG1s was collected by centrifugation for 1 min at 500 g . Next, to analyze and profile the released Fab fragments, we employed a reversed-phase liquid chromatography coupled mass spectrometry (LC-MS) and data processing method, as previously described. , Details about the LC-MS experiment and subsequent data processing method are described in Experimental S1 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding these challenges, we need to distinguish antibodies at the clonal level to better understand the immune system and find new potential candidates for monoclonal antibody (mAb) therapy development. To fill this gap, techniques that can focus at the protein level on the antibody repertoires, e.g., Ig-seq , and liquid chromatography mass spectrometry (LC-MS)-based antibody clonal profiling, , are essential.…”
Section: Introductionmentioning
confidence: 99%
“…All our previous Ig profiling studies were performed using Orbitrap-based mass analyzers. Notwithstanding the fact that Orbitrap-based instruments are among the most used instruments for peptide- and protein-based proteomics, alternative platforms have gained traction in recent years. Among these, the timsTOF series stands out especially for its use in high-throughput peptide-centric proteomics applications in, for instance, plasma proteomics and affinity-pull-down proteomics .…”
Section: Introductionmentioning
confidence: 99%